"The Man in the Panther Skin" and "Cymbeline" - Elguja Khintibidze, (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2014)
This article represents a continuation of the research published in the previous issue of The Kartvelologist: "The Man in the Panther Skin - William Shakespeare's Literary Source". This article analyses the similarity between the plot and compositional factors of Shakespeare's Cymbeline on the one hand, and the story of Nestan and Tariel in Rustaveli's The Man in the Panther Skin (MPS) on the other. Part of the article discusses the origin and staging of Cymbeline, which still remains unresolved in Shakespeare Studies.